Analysis of The Influence of Personality and Flexible Work Arrangements on Work-Life Balance Mediated by Organizational Support at The North Medan One-Stop Manuggal Administration System (SAMSAT) Office - Prafitri Ramadhani Siregar; Nuzuliati; Emi Wakhyuni (Yayasan Multidimensi Kreatif, 2024)
The North Medan One-Stop Manuggal Administration System (SAMSAT) or known as the One-Stop Manuggal Administration System is a combination of 4 (four) agencies that have motor vehicle tax objects domiciled in North Sumatra. The problem that occurs is that in 2022 there will still be a high level of work errors made by employees. These errors can occur due to decreased employee productivity, which will then cause stress and disrupt work-life balance. This research is a quantitative study that aims to analyze the influence of personality and flexible work arrangements on work-life balance through organizational support. The population of this study is that the population in this study is all permanent employees at the North Medan Samsat. Meanwhile, the number of samples was 80 respondents. The analysis technique used is Partial Least Square (PLS), which is a component or variant-based Structural Equation Model (SEM). The results of the research, data prove that personality influences organizational support with a p-value of 0.000, flexible working hours arrangements influence organizational support with a p-value of 0.002, organizational support influences work-life balance with a p-value of 0.000 , personality influences work-life balance with a p-value of 0.012 and flexible working hours arrangements influence work-life balance with a p-value of 0.000. Then, the results of the mediation test show that personality influences work-life balance through organizational support with a p-value of 0.000 and flexible work arrangements influence work-life balance through organizational support with a p-value of 0.004.